2014
DOI: 10.1093/geronb/gbu164
|View full text |Cite
|
Sign up to set email alerts
|

Living Arrangements and Health of Older Adults in India

Abstract: Our study demonstrates that multigenerational households--the traditional and the most dominant form of living arrangement in India--have protective health benefits for older adults, while taking into account potential selection mechanisms. On Contrary to some epidemiological studies, we do not find any elevated risk of exposure to short-term illness, when older adults are living in households with young grandchildren.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
93
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 106 publications
(96 citation statements)
references
References 31 publications
3
93
0
Order By: Relevance
“…Due to social isolation and lack of social support, living alone has profound effect on the health status of an older person [20] and consequently on their use of health services [21]. Many studies have shown that an elderly living alone was at a higher risk of becoming ill, having difficulty with instrumental activities of daily living, worsening mobility, and suffering from depression [22] [23]. Furthermore, evidences from developed countries indicated that those living alone or having weak social relationships showed higher likelihood of health facility utilization [24] [25] [26].…”
Section: Introductionmentioning
confidence: 99%
“…Due to social isolation and lack of social support, living alone has profound effect on the health status of an older person [20] and consequently on their use of health services [21]. Many studies have shown that an elderly living alone was at a higher risk of becoming ill, having difficulty with instrumental activities of daily living, worsening mobility, and suffering from depression [22] [23]. Furthermore, evidences from developed countries indicated that those living alone or having weak social relationships showed higher likelihood of health facility utilization [24] [25] [26].…”
Section: Introductionmentioning
confidence: 99%
“…From the interview, it was found that the majority (83.8%) of the respondents, in their old age, prefer to live independently or with their spouse in their own homes. This finding is different from the established evidence that suggests Asian families were dominated by the choice of the living arrangement with extended families (Chen & Chen, 2012;Munsur et al 2010; Samantha et al, 2015;Sereny, 2011). The remaining chose to live with children, families, relatives, friends, live in formal care or other informal institutions.…”
Section: Descriptive Analysismentioning
confidence: 61%
“…Previously, the western family arrangement which is governed by a nuclear family structure, may differ to that of an Asian arrangement which is dominated by extended families or multigenerational households. For example, in Bangladesh and India, the responsibility for welfare of the elderly depends on their adult children and the state has less obligation in providing care for them (Munsur, Tareque, & Rahman, 2010;Samantha, Chen, & Vanneman, 2015). However the trend is now moving towards the western model.…”
Section: Literature Reviewmentioning
confidence: 99%
“…However, the dimension of socioeconomic, such as economic and living statuses of older adults, is relatively understudied. Previous studies have shown that older adults’ health is correlated with family wealth and living arrangements . Furthermore, economic status influences living arrangements, and both economic status and living conditions influence older adults’ well‐being .…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have shown that older adults' health is correlated with family wealth and living arrangements. 10 Furthermore, economic status influences living arrangements, 11 and both economic status and living conditions influence older adults' well-being. 12 Therefore, the socioeconomic dimension of aging should be equally valued alongside the more commonly discussed physical and psychological dimensions.…”
Section: Introductionmentioning
confidence: 99%